"Three-Circle Model" under the Green Development. Issue 5 (February 2019) - Wu, Yusi; Wang, Yisheng; Chen, Hui
Abstract: In order to promote the new normal of green development and continuously meet the growing needs of the people, this paper builds a "three-circle model" of the green development indicator system: Green Wealth - Green Growth - Green Welfare. Green wealth mainly refers to the green development of the ecological environment. Green growth mainly refers to the level of green economy development, and green welfare mainly refers to the green indicators of society. This paper analyzes the symbiosis and interactivity of ecosystems, economic systems, and social systems from the whole to the local.